2019
DOI: 10.1002/jbm.a.36856
|View full text |Cite
|
Sign up to set email alerts
|

Systematic in vitro biocompatibility studies of multimodal cellulose nanocrystal and lignin nanoparticles

Abstract: Natural biopolymer nanoparticles (NPs), including nanocrystalline cellulose (CNC) and lignin, have shown potential as scaffolds for targeted drug delivery systems due to their wide availability, cost-efficient preparation, and anticipated biocompatibility. As both CNC and lignin can potentially cause complications in cell viability assays because of their ability to scatter the emitted light and absorb the assay reagents, we investigated the response of bioluminescent (CellTiter-Glo ® ), colorimetric (MTT ® an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 56 publications
0
28
0
3
Order By: Relevance
“…[109] Thea uthors developed nuclear imaging probes by labelling the REGs with ah ydrazine-modified diagnostic radionuclide (DOTA = 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid), which displayed good biocompatibility in the cell models.I n al ater study,t he DOTAl abeling was complemented with af luorescent dye (cyanine 5), enabling systematic investigations of the nanoparticle biodistribution in vivo by nuclear and optical imaging. [151] Figure 8. a) Cryo-EM micrograph of patchy PMETAC-grafted CNCs labelled with Au 0 NPs.…”
Section: Janus-type Colloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[109] Thea uthors developed nuclear imaging probes by labelling the REGs with ah ydrazine-modified diagnostic radionuclide (DOTA = 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid), which displayed good biocompatibility in the cell models.I n al ater study,t he DOTAl abeling was complemented with af luorescent dye (cyanine 5), enabling systematic investigations of the nanoparticle biodistribution in vivo by nuclear and optical imaging. [151] Figure 8. a) Cryo-EM micrograph of patchy PMETAC-grafted CNCs labelled with Au 0 NPs.…”
Section: Janus-type Colloidsmentioning
confidence: 99%
“…On the other hand, Meesorn et al demonstrated that adsorbing as mall amount of amphiphilic poly(vinyl alcohol) onto CNCs aids their dispersion in different matrices and leads to as uperior enhancement of the mechanical performance,a rguably because hydrogenbonding interactions are maintained. [149][150][151]158] CNCs that are only partially decorated with a(covalently attached) compatibilizer may offer similar physico-chemical features,i .e., an increased dispersibility vis-à-vis unmodified CNCs and an unmitigated ability to interact with their environment through an abundance of hydrogen bonds.…”
Section: Nanocompositesmentioning
confidence: 99%
“…In einem späteren Beitrag wurde die DOTA-Markierung durch einen fluoreszierenden Farbstoff (Cyanin 5) ergänzt, was systematische Untersuchungen der Bioverteilung der Nanopartikel in vivo durch nukleare und optische Bildgebung ermçglichte. [151] 6.3. Nanokomposite CNFs und CNCs wurden umfassend als biobasierte,l eistungsfähige Verstärkung fürP olymerkomposite erforscht.…”
Section: Angewandte Chemieunclassified
“…Die Autoren entwickelten durch Markierung der REGs mit einem Hydrazin‐modifizierten diagnostischen Radionuklid (DOTA=1,4,7,10‐Tetraazacyclododecan‐1,4,7,10‐tetraessigsäure) nukleare Bildgebungssonden, die eine gute Biokompatibilität in Zellmodellen zeigten. In einem späteren Beitrag wurde die DOTA‐Markierung durch einen fluoreszierenden Farbstoff (Cyanin 5) ergänzt, was systematische Untersuchungen der Bioverteilung der Nanopartikel in vivo durch nukleare und optische Bildgebung ermöglichte [151] …”
Section: Materialperspektiven Endgruppen‐selektiver Modifizierungenunclassified
See 1 more Smart Citation